PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS MODEL DICOVERY LEARNING PADA MATERI BANGUN RUANG SISI LENGKUNG UNTUK SISWA KELAS IX TINGKAT SMP/MTs - Yulistiawati, Yulistiawati; Heleni, Susda; Hutapea, Nahor Murani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the results of observations and interviews conducted by researchers in schools on learning tools used by teachers who do not show learning activities that involve students directly in finding and applying mathematical concepts in accordance with the demands of the 2013 curriculum. Therefore, the researcher develops the learning tools of mathematics in the form of syllabus, the learning implementation plan and the student worksheet based on discovery learning model with valid and practical for curved face three dimensional objects topic. This research and development use development model ADDIE. The steps of this research and development are need analysis, collect the reference, design the learning tools of mathematic, develop the learning tools of mathematic, validated by three validators and further revised based on the input from validators. The revised is test to small group consist of nine students of class IX SMP Negeri 1 Pekanbaru. The result of data analysis from the developed mathematics learning tools shows the average of syllabus valisation is 2.96, the average validation of the learning implementation plan is 3.34, the average validation of the student worksheet is 3.25, and the practical level of the student worksheet is 83.23 %. Based on the analysis of data and discussion can be concluded that learning tools developed in the form of syllabus, the learning implementation plan and the student worksheet have been assessed valid after through the validation process and the student worksheet are developed also have qualified practicality for students use class IX after going through the test phase.Key words: Learning Tools of Mathematic, Development, Discovery Learning Models, Curved Face Three Dimensional Objects